Znanstvenoraziskovalno in raziskovalno-razvojno delo v Bosni in Hercegovini s posebnim ozirom na pomen in vlogo univerzitetnih knjižnic - Ovčina, Ismet (Organizacija znanja, 2006)
Even ten years after the war, the state of science and higher education in Bosnia and Herzegovina remains critical, as discovered by a UNESCO expert group, which prepared a special document on this topic. This tiggered the preparation of the "Strategy for scientific and technological development of Bosnia and Herzegovina" which symbolises a great step in the right direction. The great importance of libraries, especially higher education libraries, for the successful implementation of the Bologna guidelines has been recognised. Several prerequisites for a quick restoration of science and higher education are still missing, in particular a state-of-the-art research infrastructure. Crucial in this respect is the COBISS.BH system, which is being restored successfully after the disruption, even though not all the issues regarding status and finances have been resolved yet.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; raziskave; visokošolske knjižnice; znanstveno delo